Price Effects in the Evaluation of Investment Projects - Suslov, Victor I.; Novikova, Tatyana S.; Gulakova, Olga I. (Economy of Regions, 2021)
In the context of globalisation, there is a need to assess the difference between domestic and world price effects as an important component of the economic analysis of investment projects. We developed an integrated approach to measuring the differences between commercial and public efficiency (indicating price effects) and substantiating the application of specific mechanisms for implementing relevant projects based on the principles of public-private partnership. We propose to estimate price effects using three interrelated models: financial and economic model, input-output multi-regional model, and econometric model. The combination of these models allows analysing large investment projects considering their influence on the development trends of the global, national and regional economy. This methodology was tested on the example of a real regional project for the construction of the Eastern Siberia - Pacific Ocean (ESPO-2) oil pipeline. The results show that the share of price effects amounted to more than 35 % of net present value within the framework of public efficiency, confirming their high significance. Tax price effects have the largest share in the structure of the price effects. Indirect price effects of the considered project are less significant. The research results have confirmed that the identification of indicators of public efficiency and in-depth analysis of price effects increase the validity of the assessment of regional infrastructure projects. In the future, we plan to use the proposed methods as an integral part of a comprehensive assessment of large-scale production, transport and research infrastructure projects.